(untitled) (AYUSHDHARA, 2017)
India is a country where different type of languages, culture & food habits are in use. There is tremendous regional diversity in their daily diets. Indian cuisine reflects a more than 5,000 year history of various groups and cultures interacting with the subcontinent, leading to diversity of flavors and regional cuisines found in modern-day India. Dietary pattern analysis is an emerging area of research. This study demonstrates the importance of elucidating the social and cultural contexts in which dietary behaviors exist, especially when considering contradictory mainstream approaches to health promotion. Most of the food items were developed by keeping the health aspect in mind and some of the foods were directly used as homemade medicine for some specific diseases as they had therapeutic value. The previous generations knew very well the medicinal value of some of the spices or other ingredients and as such made it a point to use that ingredient in some food recipe to add medicinal value in it. This made Indian cuisine rich in a wide variety and taste and also helpful for health. It also provides valuable information to develop qualitative measures for empirical assessment, develop and evaluate targeted interventions.